Makna dan Fungsi Penamaan Dhapur Keris yang Mengandung Nama Tokoh dan Pusaka Wayang Purwa - Vebrianto, Bernadus; Sulanjari, Bambang; Sunaryo, Sunaryo (Universitas PGRI Semarang, 2021)
The goal of this study is to explan the significance and function of naming dhapur keris, which holds the names of figures and puppet legancy. The research employed falls under the genre of semantic research, which examines the meaning of a word. In addition and matching algorithms, the applied methodology takes a qualitative descriptive approach. The name of dhapur keris, which comprises the names of characters and the heritage of wayang purwa, was used as the source of data in this study, and data was collected utilizing nterview and documentation procedures. Data reduction prcedures, data presentation, and conclusions are then used to analyze the results. The basic naming of dhapur keris, which contains (1) the name of the figure and (2) the name of wayang purwa legacy based on the meaning and function behind the formation of dhapur keris, was discoverad based on the results of data analysis. Although there are some roles that are comparable between dhapur and oneanother, dhapur keris have various meanings. The meaning behind the construction of dhapur keris Anoman, Bima, Karna, Pandawa, Pasupati, Pulanggeni has aspects of authority (3), dhapur Semar has a close rel ationship with the area of love, leadership, and protection (4), and dhapur Kala, on the other hand, is closely associated with the realm of religion. All praise is due to Allah (5).